Dance as Openig of the Worlds - Marcelli, Miroslav (Iluminace, 2001)
An analysis of the work of director Vincente Minnelli using his musical An American in Paris as an example.
Keywords: American director; An American in Paris 1951; dance in film; dance film; film musical; film analysis